2006
DOI: 10.1080/14786430500341243
|View full text |Cite
|
Sign up to set email alerts
|

Incommensurate–commensurate transition and nanoscale domain-like structure in iron doped Ti–Ni shape memory alloys

Abstract: Precursor phenomena of displacive transformation have been studied by optical and transmission electron microscope observation and X-ray diffraction of Ti-(50 À x)Ni-xFe (x ¼ 2, 4, 6, 8 in at.%) alloys. We found that a Ti-44Ni-6Fe alloy exhibits a second-order-like incommensurate-commensurate transition without latent heat and discontinuity in lattice parameters. In other words, diffuse scatterings appear in an electron diffraction pattern at an incommensurate position on cooling; they move gradually towards 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
46
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 16 publications
6
46
1
Order By: Relevance
“…The intensity of diffuse satellites increase and the position gradually shift toward commensurate position of g B2 +1/3 0> * with decreasing temperature. These results are consistent with the previous study [8].…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…The intensity of diffuse satellites increase and the position gradually shift toward commensurate position of g B2 +1/3 0> * with decreasing temperature. These results are consistent with the previous study [8].…”
Section: Methodssupporting
confidence: 83%
“…Based on these results, they concluded that a microdomain is not a small R-phase but a single transverse atomic displacement. We also investigated this behavior and reported in the paper [8]. That is we investigated the composition and temperature dependences of the diffuse satellites appearing in electron diffraction patterns of Ti-(50-x)Ni-xFe alloys (6 x 10), which exhibit a negative temperature coefficient of resistivity below a temperature T min as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…5(a)) showed a normal B2 spectrum as expected by a frozen STG. As the stress increased to about 80 MPa, the intensity of the 110 B2 peak decreased and two new peaks appeared, which can be indexed as 112 R and 300 R , being the same as those of the normal R martensite in Ti 50 Ni 48 Fe 2 alloys 21 . When the stress reached 180 MPa [the maximum stress point in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Thus it seems that the local strain order in the nano-domains is an R-like structure, being the same as the binary Ti-Ni STG 10 . The above TEM observation demonstrates during a STG transition there is a gradual increase in the size and in volume fraction of the nano-domains, which have an R-like structure 21,22 . It is the origin of the gradual broadening of the 110 B2 peak during the cooling as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…14,15) Recently, we measured electrical resistivity, magnetic susceptibility and specific heat for a series of Ti-(50 À x)Ni-xFe alloys with Fe content up to 20 at%, and found that these physical properties exhibit anomalies in the parent phase of the alloys which show the R-phase transformation and also in the alloys with Fe content more than 6 at% which do not show apparent Rphase transformation. 16,17) In addition, these anomalies are observed most in Ti-44Ni-6Fe and Ti-42Ni-8Fe alloys and gradually suppressed as Fe content increases. We believe that these anomalies can be so-called precursor phenomena.…”
Section: Introductionmentioning
confidence: 95%